Product with Sum of Scalar

From ProofWiki
Jump to navigation Jump to search

Theorem

Let $\left({G, +_G}\right)$ be an abelian group whose identity is $e$.

Let $\left({R, +_R, \times_R}\right)$ be a ring whose zero is $0_R$.

Let $\left({G, +_G, \circ}\right)_R$ be an $R$-module.


Let $x \in G, \lambda \in R$.

Let $\left \langle {\lambda_m} \right \rangle$ be a sequence of elements of $R$ i.e. scalars.


Then:

$\displaystyle \left({\sum_{k \mathop = 1}^m \lambda_k}\right) \circ x = \sum_{k \mathop = 1}^m \left({\lambda_k \circ x}\right)$


Proof

This follows by induction from Module: $(2)$, as follows.


For all $m \in \N^*$, let $P \left({m}\right)$ be the proposition:

$\displaystyle \left({\sum_{k \mathop = 1}^m \lambda_k}\right) \circ x = \sum_{k \mathop = 1}^m \left({\lambda_k \circ x}\right)$


Basis for the Induction

$P(1)$ is true, as this just says:

$\lambda_1 \circ x = \lambda_1 \circ x$

This is our basis for the induction.


Induction Hypothesis

Now we need to show that, if $P \left({n}\right)$ is true, where $n \ge 1$, then it logically follows that $P \left({n+1}\right)$ is true.


So this is our induction hypothesis:

$\displaystyle \left({\sum_{k \mathop = 1}^n \lambda_k}\right) \circ x = \sum_{k \mathop = 1}^n \left({\lambda_k \circ x}\right)$


Then we need to show:

$\displaystyle \left({\sum_{k \mathop = 1}^{n+1} \lambda_k}\right) \circ x = \sum_{k \mathop = 1}^{n+1} \left({\lambda_k \circ x}\right)$


Induction Step

This is our induction step:

\(\displaystyle \left({\sum_{k \mathop = 1}^{n+1} \lambda_k}\right) \circ x\) \(=\) \(\displaystyle \left({\sum_{k \mathop = 1}^n \lambda_k + \lambda_{n+1} }\right) \circ x\)
\(\displaystyle \) \(=\) \(\displaystyle \left({\sum_{k \mathop = 1}^n \lambda_k \circ x}\right) + \lambda_{n+1} \circ x\) Module: $(2)$
\(\displaystyle \) \(=\) \(\displaystyle \sum_{k \mathop = 1}^n \left({\lambda_k \circ x}\right) + \lambda_{n+1} \circ x\) Induction hypothesis
\(\displaystyle \) \(=\) \(\displaystyle \sum_{k \mathop = 1}^{n+1} \left({\lambda_k \circ x}\right)\)

So $P \left({n}\right) \implies P \left({n+1}\right)$ and the result follows by the Principle of Mathematical Induction.


Therefore:

$\displaystyle \forall m \in \N^*: \left({\sum_{k \mathop = 1}^m \lambda_k}\right) \circ x = \sum_{k \mathop = 1}^m \left({\lambda_k \circ x}\right)$

$\blacksquare$


Also see


Sources